Life-cycle GHG assessment of carbon capture, use and geological storage (CCUS) for linked primary energy and electricity production. (November 2015) - Lacy, Rodolfo; Molina, Mario; Vaca, Mabel; Serralde, Carlos; Hernandez, Graciela; Rios, Gerardo; Guzman, Erika; Hernandez, Ruben; Perez, Ricardo
Highlights: GHG emissions and GWP impact estimates obtained through LCA for a CCUS system. GWP estimates for natural gas supply, generation of electricity and CCUS stages. Natural gas supply and electricity generation stages had largest CO2 e estimates. NGCC + CCUS GWP impact similar to the GWP in a 50 MW geo-thermal plant. CO2 leakage variable increased the GWP impact when modified slightly. Abstract: Carbon capture, use and geological storage (CCUS) could be feasible when fossil fuel-power plants are close to oil and gas reservoirs where CO2 -enhanced oil recovery (EOR) technologies are applicable. In this research, we used a novel "well-to-well" approach that included the operations from natural gas production at oil field to CO2 injection for EOR operations at depleted oil fields. This paper includes estimates for greenhouse gas (GHG) emissions arising from a hypothetical CCUS case with a natural gas combined cycle power plant (NGCC) and Global Warming Potential (GWP) impact, by using Life-Cycle Assessment (LCA) methodology. Our research comprises a comparison with other electricity-generation technologies, including super critical pulverized carbon (SCPC), NGCC without CO2 capture, geothermal, mini-hydro, wind and nuclear. The LCA stages that were undertaken in this study were natural gas supply system, electricity generation, CO 2 capture, CO 2 transport, EOR operations and environmental monitoring . Three different functional units were used in this study: MJ, kW h and produced oil barrel (bbl). Results indicate that the energy produced by the described CCUS system had an environmental impact on climate change (global warming potential) of 0.044 kg CO2 e/MJ. The NGCC power plant with carbon capture unit would produce 0.177 kg CO2 e/kW h, representing about 21% and 36% of the estimated values for the SCPC and NGCC (without CCS) cases respectively, and about 24% less greenhouse gas emissions than the geothermal scenario. The oil produced in the EOR stage had a greenhouse gas emission rate of 38 kg CO2 e per oil barrel and 251 kg CO2 e per oil barrel in the whole CCUS system.